Da posse a resistência: os desafios da Comunidade de Fundo de Pasto Caladinho na defesa do território - Lima, Vanderlei Rocha (2018)
The contest over possession and use of land, as well the natural resources which are still available, has generated physical and symbolic violence, maintaining a structural arrangement: on one hand excludes thousands of workers from access to land to live and reproduce, on other, has mainly forced peasants in their diversity, indigenous people, among other populations and local communities to leave their territories. However, we see in the countryside, organized processes of resistance in the middle of territorial conflicts. Thus, this study allowed us to know how the community of Fundo de Pasto Caladinho in Curaçá City – State of Bahia faces conflicts over ownership of the collective area and how they react to protect their territory, in order to guarantee their social reproduction and maintenance of the traditional way of life, as well the actions currently developed by the State of Bahia, through land regularization applied to the territories of traditional communities of Fundo de Pasto. The methodological procedures adopted in this research allowed a survey of the history of the Caladinho community, its collective organization and its means of resistance based on the narrative and the experiences of its residents, as well a debate about its territory through cartography, whose questions addressed in this study can serve other traditional communities, especially Fundos and Fechos de Pasto.